Effectiveness of Differentiated Learning in Japanese Language Lessons: A Case Study at Private Senior High School Plus Taruna Andalan, Riau - Loka, Diah Vita (Japanology: The Journal of Japanese Studies, 2022)
This study aims to evaluate the effectiveness of differentiated learning in the subject of Japanese language in eleventh grade at SMAS Plus Taruna Andalan, Pelalawan Riau. Utilizing both quantitative and qualitative approaches through survey methods, this research examines students' experiences and satisfaction levels with differentiated learning. An initial diagnostic assessment of 27 students was conducted to identify their learning styles, which formed the basis for student grouping and the adaptation of learning activities, including projects tailored to the needs of each learning group. Data were collected through observation, document analysis, and questionnaires, and analyzed thematically and quantitatively to evaluate the effectiveness of this learning method. The conclusion of this study indicates that differentiated learning has proven to be quite effective in this context, with the majority of students showing a positive response. This approach successfully accommodated different learning styles and encouraged a positive learning experience among students, though there is an indication that there is still room for improvement in its effectiveness. More than 88% of students felt happy or very happy with this method, yet only 8% expressed complete satisfaction, signaling a need for further efforts to enhance the implementation of differentiated learning in the future.